Changing to remote management of a community heart failure population during COVID-19 – Clinician and patient perspectives'. (December 2020) - Kerr, Brian; Pharithi, Rebabonye B.; Barrett, Matthew; Halley, Carmel; Gallagher, Joe; Ledwidge, Mark; McDonald, Kenneth
Abstract: Background: The COVID pandemic has challenged the traditional methods used in care of patients with heart failure (HF). Remote management of HF patients has been recommended in order to maintain routine standards of care, but satisfaction with this platform of care is unknown. We set out to address the physician and patient opinion of remote management of HF during COVID-19. Methods and Results: An observational report of the use of a Structured Telephonic assessment (STA) in stable outpatient HF patients. Physician grading of the STA was complemented by 100 randomly chosen patients to ascertain patient satisfaction and comment. 278 patients underwent a STA. Patient preference for STA was noted in 66%. Convenience was the single most cited reason for this preference (83.3%). The STA was deemed satisfactory by clinicians in 67.6%. The two-leading reasons for clinician dissatisfaction were data gaps providing a barrier to titration (55.6%) and need for clinical exam (18.9%). The annual review appointment visit subtype possessed the highest levels of satisfaction congruence amongst both clinicians and patients. Conclusion: In summary, this report demonstrates reasonable patient / physician satisfaction with STA, and provides some direction on how this care platform might be sustained beyond the COVID crisis.